Fluvial organic carbon composition regulated by seasonal variability in lowland river migration and water discharge - Golombek, Nina Y. (2021)
Identifying drivers of seasonal variations in fluvial particulate organic carbon (POC) composition can aid sediment provenance and biogeochemical cycling studies. We evaluate seasonal changes in POC composition in the Río Bermejo, Argentina, a lowland river running ∼1,270 km without tributaries. Weekly POC concentration and isotopic composition from 2016 to 2018 show that during the wet season, increased lateral channel migration generates an influx of 13C-enriched and 14C-enriched floodplain-sourced material, overprinting the 13C-depleted and 14C-depleted headwater signature that is observed during the dry season. These findings demonstrate how channel morphodynamics can drive variability of POC composition in lowland rivers, and may modulate the composition of POC preserved in sedimentary archives.